Power Doppler Quantification in Assessing Gestational Trophoblastic Neoplasia - Li, Yuanwei; Tang, Meng Xing; Agarwal, Roshan; Patel, Daksha; Eckersley, Robert J.; Barrois, Guillaume; Roddie, Mary E.; Dayal, Linda; Savage, Philip M.; Seckl, Michael J.; Lim, Adrian (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Purpose The FIGO score cannot accurately stratify low-risk gestational trophoblastic neoplasia (GTN) patients who develop chemoresistance to single agent methotrexate chemotherapy. Tumour vascularisation is a key risk factor and its quantification may provide non-invasive way of complementing risk assessment.Materials and Methods 187 FIGO-staged, low-risk GTN patients were prospectively recruited. Power Doppler ultrasound was analysed using a quantification program. Four diagnostic indicators were obtained comprising the number of colour pixels (NCP), mean dB, power Doppler quantification (PDQ), and percentage of colour pixels (%CP). Each indicator performance was assessed to determine if they could distinguish the subset of low-risk patients who became chemoresistant.Results There were 111 non-resistant and 76 resistant patients. NCP performed best at distinguishing these two groups where the non-resistant group had an average 3435 (± 2060) pixels and the resistant group 6151 (± 3192) pixels (p < 0.001). PDQ and %CP showed significant differences (p < 0.001) but had poorer performance (area under ROC curves were 72 % and 67 % respectively compared with 75 % for NCP). The mean dB index was not significantly different (p = 0.133).Conclusion Power Doppler ultrasound quantification shows potential for non-invasive assessment of tumour vascularity and can distinguish low-risk GTN patients who become chemoresistant from those who have an uncomplicated course with first line treatment.
Keywords: uterus; ultrasound-power doppler; angiogenesis; neoplasms; tumor